Brief Report: Anakinra Use During Pregnancy in Patients With Cryopyrin‐Associated Periodic Syndromes1. Issue 11 (November 2014) - Chang, Zenas; Spong, Catherine Y.; Jesus, Adriana A.; Davis, Michael A.; Plass, Nicole; Stone, Deborah L.; Chapelle, Dawn; Hoffmann, Patrycja; Kastner, Daniel L.; Barron, Karyl; Goldbach‐Mansky, Raphaela T.; Stratton, Pamela
<x xml:space="preserve">Abstract</x> Objective To describe the pregnancy course and outcome and the use of anakinra, a recombinant selective interleukin‐1 receptor blocker, during pregnancy in patients with cryopyrin‐associated periodic syndromes (CAPS), including familial cold autoinflammatory syndrome (FCAS), Muckle‐Wells syndrome (MWS), and neonatal‐onset multisystem inflammatory disease (NOMID). Methods Women with CAPS who were currently enrolled in natural history protocols and had been pregnant were included. Subjects underwent a structured, standardized interview with regard to maternal health, pregnancy, and fetal outcomes. Medical records were reviewed. Results Nine women (4 with FCAS, 2 with MWS/NOMID overlap, and 3 with NOMID) reported 1–4 pregnancies (a total of 15 pregnancies in women with FCAS, 3 in women with MWS, and 6 in women with NOMID). Six births to women with FCAS and 3 births to women with NOMID or MWS/NOMID overlap occurred while the patients were receiving anakinra. In women who became pregnant while taking anakinra, the anakinra treatment was continued; the prepregnancy dosage was maintained except in the case of 1 woman whose dosage was increased during a pregnancy with twins. No preterm births or serious complications of pregnancy were observed. One fetus of the twin pregnancy had renal agenesis and died in utero. Genetic testing showed that the deceased twin carried the same NLRP3 c.785T>C, p.V262A mutation as the mother. The other twin was healthy and mutation negative. Conclusion Anakinra was continued during pregnancy in women with CAPS and provided significant, persistent symptom relief while continuing to prevent the long‐term sequelae of CAPS. Anakinra was well tolerated. Although a causal relationship between anakinra and renal agenesis seems unlikely, further safety data are needed.